2022
DOI: 10.3389/fonc.2022.910470
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA-Associated CeRNAs Regulatory Axes in Retinoblastoma: A Systematic Scoping Review

Abstract: Retinoblastoma (RB) is one of the most common childhood cancers caused by RB gene mutations (tumor suppressor gene in various patients). A better understanding of molecular pathways and the development of new diagnostic approaches may lead to better treatment for RB patients. The number of studies on ceRNA axes is increasing, emphasizing the significance of these axes in RB. Circular RNAs (circRNAs) play a vital role in competing endogenous RNA (ceRNA) regulatory axes by sponging microRNAs and regulating gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 167 publications
(220 reference statements)
0
5
0
Order By: Relevance
“…[ 28 ] There are many miRNA binding sites on circRNAs that specifically bind to a certain sequence of the target miRNA through base complementation, thus acting as a miRNA sponge. [ 29 ] Studies in the cardiovascular field have indicated that circRNAs largely function via ceRNA mechanisms as mediators of biological phenotypes. For example, circRbms1 can attenuate the development of cardiac I/R injury by sponging miR‐92a to increase BCL2L11 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] There are many miRNA binding sites on circRNAs that specifically bind to a certain sequence of the target miRNA through base complementation, thus acting as a miRNA sponge. [ 29 ] Studies in the cardiovascular field have indicated that circRNAs largely function via ceRNA mechanisms as mediators of biological phenotypes. For example, circRbms1 can attenuate the development of cardiac I/R injury by sponging miR‐92a to increase BCL2L11 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs are exceptionally stable regulatory molecules inside the cell because they are immune to exonuclease actions (Xie et al, 2017 ). CircRNAs have been characterized as protein decoys, scaffolds, and recruiters, as well as transcriptional regulators, miRNA sponges, and protein templates (Zhou W. Y. et al, 2020 ; Asadi et al, 2022 ). CircRNAs have an active role in muscular tissue formation (Legnini et al, 2017 ), synapse formation and activity field (Chen et al, 2019 ), neuronal gene expression regulation (van Rossum et al, 2016 ), and CNS differentiation and development (Mehta et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CeRNAs are transcripts composed of messenger RNA (mRNAs) and non-coding RNAs (ncRNAs) that contest for shared microRNAs (miRNAs) to cross-regulate one another (Asadi et al, 2022 ). Franco-Zorrilla et al reported a process known as “target mimicry,” which occurs when a non-coding RNA in plants sequesters miR-399 and de-represses its target (Franco-Zorrilla et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs act as ceRNAs to regulate several biological processes as cell proliferation, apoptosis, invasion, and migration. The term' ceRNA' was created in 2011 to characterize this additional layer of posttranscriptional control [63].…”
Section: The Cernas Axes In Rbmentioning
confidence: 99%